IoT-based smart waste management for environmental sustainability - Acharya, Biswa Ranjan; Dey, Satarupa; Zidan, Mohammad (Boca Raton, FL : CRC Press, 2022)
"This book consolidates and summarizes smart technologies like IoT, edge computing, and AI used in different aspects of waste material management, mitigation, and recycling for a sustainable environment. One of the cases explains how IoT-based systems and wireless sensors can be used to continuously detect common pollutants such as volatile organic compounds (VOCs), carbon monoxide, and particulate matter (PM) and how the data collected are used to assess the overall air quality and determine actions for improvements. A collection of practical case studies, this book provides a comprehensive knowledge in smart waste management to readers in universities, research centers, and industries"--
E-waste management / Babita Panda, Gyanendra Kumar Panda, Arjyadhara Pradhan -- Waste prevention : its impact and analysis / Arjyadhara Pradhan, Sarita Samal, Babita Panda, Biswaranjan Acharya -- Smart waste bin using AI, big data analytics and IoT / Nivedita Das, Jyotiprakash Panigrahi, Chandrima Roy, Biswaranjan Acharya.
OCLC-licensed vendor bibliographic record.
Keywords: Integrated solid waste management -- Automation; Refuse and refuse disposal -- Automation; Internet of things; TECHNOLOGY / Engineering / Civil; COMPUTERS / Artificial Intelligence